Migration behaviour of twaite shad Alosa fallax assessed by otolith Sr:Ca and Ba:Ca profiles. Issue 6 (15th May 2013) - Magath, V.; Marohn, L.; Fietzke, J.; Frische, M.; Thiel, R.; Dierking, J.
<x xml:space="preserve">Abstract</x> Individual migration behaviour during the juvenile and adult life phase of the anadromous twaite shad Alosa fallax in the Elbe estuary was examined using otolith Sr:Ca and Ba:Ca profiles. Between hatching and the end of the first year of life, juveniles showed two migration patterns. Pattern one exhibited a single downstream migration from fresh water to the sea with no return into fresh water. In contrast, pattern two showed a first migration into the sea, then a return into fresh water and, finally, a second downstream migration into marine water. This first report of migration plasticity for A. fallax points to different exposure times to estuarine threats depending on the migration strategy. In adults, high Sr:Ca and low Ba:Ca in the majority of individuals confirmed prior reports of a primarily marine habitat use. Patterns reflecting spawning migrations were rarely observed on otoliths, possibly due to the short duration of visits to fresh water.